PENGARUH MUTASI DENGAN RADIASI SINAR GAMMA (Co60) TERHADAP PRODUKTIVITAS JAMUR TIRAM ABU-ABU (Pleurotus sajur-caju) - Ira Djajanegara; Priyo Wahyudi; Donowati Tjokrokusumo; Netty Widyastuti; Harsoyo Harsoyo (The East Java Biological Society, 2007)
Irradiation aplied to living organisms may have positive or negative effects on physiological and morphological properties of the organisms. One way to gain genetic variation with better properties than the parental strain is by Gamma (Co 60) radiation application. During this experiment, Gama (Co 60) rays was applied to the grey oyster (Pleurotus sajur-caju) mushroom mycellia during exponential phase. Radiation was applied at 0.75 KGray with dose velocity of 1.149 KGray. Analysis of mushroom productivity performances indicate that diameter of mycellia, fresh weight, dry weight, diameter of fruit body and the amount of fruit body of the mutant and control were not significantly different. However, the isozyme pattern showed a different pattern between the mutant and the control which indicates that mutation process has already occured. These data show that mutation did not affect the productivity of the mushroom. Therefore, mutation may affect the nutritional quality of the mushroom instead. Further experiment to verify this possibility is suggested.